Reflections on Inter-University Collaboration to Deliver an Graduate Certificate in Evaluation to Government of the Northwest Territories Employees - McDavid, Jim C. (Canadian Journal of Program Evaluation, 2020)
This practice note describes and reflects on an inter-university collaboration to deliver a graduate credential in evaluation to Government of the Northwest Territories (GNWT) staff . The collaboration involved faculty members from two member institutions of the Consortium of Universities for Evaluation Education (CUEE). We describe the process of negotiating a contractual agreement, developing and delivering the program, and offer our reflections and lessons learned. Overall, this sort of collaboration is worthwhile but is challenging to implement in conditions where universities encourage student movement across institutional boundaries but, at the same time, are much less supportive of program to program collaborations across these boundaries.